Compromise and arrangement between a company and its creditors and/or members in terms of Section 311 of the Companies Act no. 61 of 1973, as amended - Truter, Hendrik Christiaan (Department of Commercial Law, 2021)
The need often arises for a company to negotiate an agreement with its members and/or creditors, in order to modify an existing set of circumstances affecting the interests of the parties to the agreement (1). In certain circumstances the situation arises where due to large numbers involved, or unwillingness to participate in such an agreement difficulties are experienced to enter into and conclude negotiations with every single member or creditor. Accordingly, the legislature has laid down a statutory procedure in Section 311 of the Companies Act No 61 of 1973 in order to achieve the desired result. In terms of the section, a company can, subject to the supervision of the courts, bind its members and/or creditors to proposals agreed to by a majority of them. The terms of the section, such as "arrangement" and "compromise" have been the subject of several court decisions. Furthermore, in order to achieve a desired result, the terms of the section often have to be viewed in conjunction with provisions contained in the Companies Act itself, as well as other legislation. The compromises and arrangements referred to in the section have a wide application as expounded by court decisions (2) and commercial practice (3). The procedure to obtain the sanctioning thereof, is laid down in the Companies Act (4), and is to be seen in conjunction with the Rules concerning procedural conduct in the courts, as well as procedural precedent. -2 - A standard scheme was developed in our practice for the achievement of an arrangement or compromise in terms of Section 311, (5) and applications for the sanctioning of such schemes were granted for a number of years as a matter of routine. The practice and industry active in the field was thereafter thrown into some confusion especially in the Transvaal and the Cape Province, primarily in view of the fact that the courts could find no active involvement of the company in a standard scheme (6). As a result of this various alternative schemes were devised in an effort to obtain the sanction of the courts in terms of section 311. The Appellate Division has now in the matter of Namex (7) heralded a return to the standard scheme in our law. In reflecting upon the above issues this dissertation will refer to the historical background to the Namex case, in view of the existence of schemes persuant to the decisions in Robin and Multi-Bou. Furthermore, decisions involving the legislation ancillary to Section 311 will also be briefly dealt with.